Changes in shooting accuracy among basketball players under fatigue: a systematic review and meta-analysis - Li, S.; Luo, Y.; Cao, Y.; Li, F.; Jin, H.; Mi, J. (Frontiers in Physiology, 2025)
Objective: To investigate the influence of physical and mental fatigue of different intensities (mild, moderate or severe) on basketball shooting accuracy, with the aim of informing more effective training protocols and competition strategies.